2016
DOI: 10.1002/path.4770
|View full text |Cite
|
Sign up to set email alerts
|

Cdkn2asuppresses metastasis in squamous cell carcinomas induced by the gain-of-function mutantp53R172H

Abstract: p53 (TP53) is the most frequently mutated gene in squamous cell carcinomas (SCCs) of the skin and head and neck. Certain p53 mutations are oncogenic and promote invasion and metastasis in SCCs. However, it is unclear how the oncogenic function of mutant p53 is modulated by other molecular alterations that co-exist in SCCs. Here, we show that deletion of the p53 gene and activation of an endogenous p53(R172H) gain-of-function mutation in the skin induce carcinomas with similar kinetics and penetrance. Deletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…GEMMs enable the editing of specific genes through the activation or overexpression of oncogenes and the inactivation or silencing of tumor-suppressor genes. The pathological changes in these GEMMs, including hyperkeratosis, abnormal hyperplasia, carcinoma in situ, and invasive carcinoma (180)(181)(182)(183)(184), are similar to those of primary OSCC in humans and 4NQO-induced OSCC in mice. By the age of 5-6 months, histologic examination of L2D1 + /p53 +/− and L2D1 + /p53 −/− mice revealed hyperkeratosis, hyperplasia, severe epithelial dysplasia, and even cancer (181).…”
Section: Characteristics Of Gemmsmentioning
confidence: 73%
“…GEMMs enable the editing of specific genes through the activation or overexpression of oncogenes and the inactivation or silencing of tumor-suppressor genes. The pathological changes in these GEMMs, including hyperkeratosis, abnormal hyperplasia, carcinoma in situ, and invasive carcinoma (180)(181)(182)(183)(184), are similar to those of primary OSCC in humans and 4NQO-induced OSCC in mice. By the age of 5-6 months, histologic examination of L2D1 + /p53 +/− and L2D1 + /p53 −/− mice revealed hyperkeratosis, hyperplasia, severe epithelial dysplasia, and even cancer (181).…”
Section: Characteristics Of Gemmsmentioning
confidence: 73%
“…2b, c ), which is an M-phase cyclin regulating the metaphase/anaphase transition, suggesting that shPRC1 possibly induces a non-metaphase mitotic arrest. Recent study suggests that in p53-null or p53-mutated cancer cells, p14ARF may partly compensate the tumor suppressor role of p53 18 , 19 . Consistently, we observed that p14ARF and cell cycle inhibitor p21 were both upregulated by shPRC1 in Hep3B (p53-null) and HuH-7 (p53-loss-of-function-mutation) cells by Ad-shPRC1 (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The value of TP53 mutation in diagnosis is different between subtypes. Some are associated with more aggressive HNSCC phenotypes, whereas others are linked with a more indolent pattern of tumor progression 26…”
Section: Introductionmentioning
confidence: 99%